Pengembangan Peralatan Eksperimen Gerak Lurus Beraturan (GLB) Berbasis Smartphone - Kakay, Pricillia Patrecia; Renyaan, Novie Evelyn; Ririhena, Yohana; Latununuwe, Altje; Huliselan, Estevanus Kristian; Singerin, Sarlota (Pattimura University, 2022)
Smartphone-based experimental equipment has been successfully developed for measuring a straight motion at a constant velocity. Read the data that comes out on the smartphone using the Accelerator Monitor software. The data is in graphic form. From the graph, it can be seen that the acceleration is zero. Furthermore vary the displacement distance, which is 100 cm and 130 cm to measure the velocity of the toy cars. The results showed that the time taken was 5 seconds and 6.5 seconds respectively for a displacement of 100 cm and 130 cm. The calculation of the velocity value for both displacements is the same value of 20 cm⁄s. This shows that the velocity value is constant which is equal to the graph results showing zero acceleration.